(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this article, mathematical modeling of the synthesis of acetylene hydroxyacid by condensation of acetylene alcohol with monochloric acid in the presence of triethylamine is carried out. The results obtained were compared with the results of the synthesis of acetylene hydroxy acid by the method of the experiment.